PERANCANGAN KAPAL TANKER 1600 DWT KECEPATAN 13 KNOT DENGAN RUTE PELAYARAN PLAJU (PALEMBANG) - TANJUNG PRIOK (JAKARTA) - Aditia Risky Dharmawan, (2020)
Indonesia is a country that needs oil products such as petroleum, because petroleum become one of the commodities for industrial components. The need for crude oil in Indonesia is about 1.4 million per day. Distribution of crude oil drilling from offshore building to inland is required by means of sea transportation. Tankers are the right means of transportation to distribute oil drilling to land. Tanker is a vessel designed to transport cargo in the form of oil. This study was designed to design 16000 DWT tanker from Plaju to Jakarta at 13 knots. The study used preliminary designs using two comparative ships. There are plenty of tanker design sequences as a general plan, hydrostatic analysis, ship construction, and ship stability.